Bio-Cooperative Approach for the Human-in-the-Loop Control of an End-Effector Rehabilitation Robot - Scotto di Luzio, Francesco; Simonetti, Davide; Cordella, Francesca; Miccinilli, Sandra; Sterzi, Silvia; Draicchio, Francesco; Zollo, Loredana (Frontiers in Neurorobotics, 2018)
The design of patient-tailored rehabilitative protocols that feature a control strategy adaptable to the user's requirements represents one of the crucial factor that influences motor recovery mechanisms such as neuroplasticity. In this scenario, including the patient in the control loop can certaintly improve functional recovery in robot-aided rehabilitation. In this paper, a novel 3D bio-cooperative robotic platform based on subject status is developed and preliminary tested on 10 healthy subjects. A novel arm-weight support system is included into an operational robotic platform for 3D upper limb robot-aided rehabilitation. The robotic platform is capable of adapting therapy characteristics on the basis of specific patient needs thanks to biomechanical and physiological measurements, thus actively including the subject in the control loop. The level of arm-weight support and of the assistance provided by the end-effector robot are varied on the basis of muscular fatigue and of biomechanical indicators, respectively, providing the correct amount of assistance based on the assistance-as-nedeed approach. Evaluation tests of the proposed platform have been carried out on 10 healthy subjects performing 3D point-to-point tasks in two different conditions, i.e. with and without assistance-as-needed. The obtained results demonstrated that the proposed platform is adaptable to the real needs of the patients by also reducing the muscular fatigue without negatively influencing motion execution.